THE ROLE OF SORONG SERAH TRADITIONAL WEDDING RITUAL OF RESILIENCE IN EAST LOMBOK - Zaenuddin Nazri; Ita Rahmania Kusumawati (Familia: Jurnal Hukum Keluarga, 2025)
The Sorong Serah traditional marriage ritual in Sembalun Bumbung Village, East Lombok, is a cultural heritage of the Sasak people that is full of moral values ​​and local wisdom. However, so far there have not been many in-depth studies that explore its symbolic meaning and social relevance amidst changes in community culture. This emphasizes the importance of this study to fill this gap. This study aims to explore in depth how the implementation of the Sorong Serah ritual can form the foundation of family resilience, both from social, emotional, and spiritual aspects. Through a qualitative approach with data collection techniques in the form of participatory observation, in-depth interviews with traditional leaders, bridal couples, and the surrounding community, and documentation studies, namely written, audio, and visual documentation. This study successfully mapped the structure and symbolic meaning in the stages of Sorong Serah. The results of the study show that Sorong Serah is not merely a symbolic ceremony, but rather an educative and affirmative means that strengthens the bonds of the nuclear family and the extended family. Research in Sembalun Bumbung Village revealed that the Sorong Serah ritual is not merely a customary ceremony, but rather an educative and affirmative means that strengthens family resilience and social cohesion. The main findings show that symbols such as kepeng in the Nyorong procession contain messages of responsibility and respect between families. Customary figures act as mediators to prevent conflict before marriage, indicating the existence of a customary-based social resolution system. The active involvement of the younger generation and the integration of customary values ​​with Islamic teachings demonstrate a dynamic and strategic cultural adaptation in preserving the meaning of this ritual amidst social change.